2019
DOI: 10.1038/s41598-019-39160-y
|View full text |Cite
|
Sign up to set email alerts
|

Point contact Andreev reflection studies of a non-centro symmetric superconductor Re6Zr

Abstract: Re 6 Zr, a non-centrosymmetric superconductor is an interesting system as recent experimental evidence suggests that the superconducting state breaks time reversal symmetry. This implies a mixing of spin singlet-triplet states leading to a complex order parameter in this system. Here, we report point contact Andreev Reflection (PCAR) measurements on a single crystal of Re 6 Zr (superconducting transition temperature (T c ) = 6.78 K). We obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…4(d). We notice that a similar contact-dependence for PCS spectra has been reported in a recent study on the non-centrosymmetric superconductor Re 6 Zr and it is ascribed to the surface superconductivity as well [51].…”
supporting
confidence: 88%
“…4(d). We notice that a similar contact-dependence for PCS spectra has been reported in a recent study on the non-centrosymmetric superconductor Re 6 Zr and it is ascribed to the surface superconductivity as well [51].…”
supporting
confidence: 88%
“…Clearly, it would be interesting to know if their SC behavior is similar to that of Re-Mo alloys. The nodeless SC scenario in ReT alloys is also supported by other techniques, as the electronic specific heat, the magnetic penetration depth measured via the tunnel-diode-oscillator-based technique, or the point-contact Andreev reflection [19,20,27,53,54,58,[64][65][66]. In addition, some studies have found evidence of twogap superconductivity in Re 0.82 Nb 0.18 and Re 6 Zr [49,66].…”
Section: Upper Critical Field and Nodeless Superconductivitymentioning
confidence: 84%
“…In all cases, the TRS breaking is manifested by the increase of σ ZF below T c . Moreover, while some studies have found evidence for two-gap superconductivity in ReX 126,127 , most measurements were generally well accounted for by a single gap s-wave model [114][115][116][123][124][125][128][129][130][131][132][133][134] . An example of this is displayed in Fig.…”
Section: Noncentrosymmetric La7x3 and Rexmentioning
confidence: 99%